Using comic strips to understand perceptions and feelings of children hospitalized due to child physical abuse - Lima, Juciara Karla de Souza; Lira, Margaret Olinda de Souza Carvalho e; Oliveira, Jeany Freire de; Campos, Fernando Vitor Alves; Paiva, Levi Olinda Lira de (Revista Cuidarte, 2021)
Introduction: Child physical abuse is a recurrent practice that harms the physical and emotional development of children. Objective: To understand the perceptions and feelings of a group of children who have been physically abused by their parents or caretakers. Materials and Methods: A descriptive qualitative study was conducted using comic strips to respond to the inductive stimulus of what comes to mind when children are mistreated. Results: Feelings of love and hate, guilt, sadness, resentment, desire for vengeance and shame were experienced, as well as the perception of physical abuse as a harmful attitude. Conclusions: Children exhibited anxiety, shyness, aggressiveness, introspection and a tendency to social isolation since child physical abuse represents a tragic episode that would ultimately lead them to death, which is why it is suggested to use dialogue or other methods of punishment instead of physical abuse.How to cite this article: Lima, Juciara Karla de Souza; Lira, Margaret Olinda de Souza Carvalho e; Oliveira, Jeany Freire de; Campos, Fernando Vitor Alves; Paiva, Levi Olinda Lira de. Uso do desenho-estória para apreensão de entendimentos e sentimentos de crianças institucionalizadas sobre agressão física. Revista Cuidarte. 2021;12(1):e1204. http://dx.doi.org/10.15649/cuidarte.1204
Keywords: Child Abuse; Punishment; Child Abandoned; Child Foster; Child Advocacy